The eurozone crisis as a balance-of-payments crisis : assessment of fundamental causes and political implications. - Boix, Vicente. (2014)
The debate over the distribution of the costs to correct the balance-of-payments disequilibrium that is at the core of the current Eurozone crisis, may create the political momentum for both current account surplus and deficit countries to leave the euro. Similar to what happened in the Bretton Woods system, there are three alternatives for balance-of-payments adjustment: deflation and recession in the debtor countries, inflation and expansion in the creditor countries, or a combination of both in order to distribute the costs of adjustment (either recession/unemployment or inflation, respectively). Surplus countries will not transfer public capital flows in the form of loans or bailouts, or implement expansionary monetary policies indefinitely in order to finance the current account deficits of Greece, Italy, Ireland, Portugal, and Spain (GIIPS), because the cost would be inflation for the former. Therefore, they will ask the GIIPS for austerity. However, deficit countries' electorates may not tolerate further painful adjustment by means of fiscal and monetary discipline, because, for them, the cost would be economic depression and rising unemployment for years. Current electoral trends in both creditor and debtor countries are explored in this paper in order to estimate their prospects of political will to leave the euro.